Earthworms and vermicompost: an eco-friendly approach for repaying nature’s debt - Singh, Archana; Karmegam, Natchimuthu; Singh, Gopal Shankar; Bhadauria, Tunira; Chang, Soon Woong; Awasthi, Mukesh Kumar; Sudhakar, Sivasubramaniam; Arunachalam, Kantha Deivi; Biruntha, Muniyandi; Ravindran, Balasubramani (Environmental geochemistry and health, 2020)
The steady increase in the world’s population has intensified the need for crop productivity, but the majority of the agricultural practices are associated with adverse effects on the environment. Such undesired environmental outcomes may be mitigated by utilizing biological agents as part of farming practice. The present review article summarizes the analyses of the current status of global agriculture and soil scenarios; a description of the role of earthworms and their products as better biofertilizer; and suggestions for the rejuvenation of such technology despite significant lapses and gaps in research and extension programs. By maintaining a close collaboration with farmers, we have recognized a shift in their attitude and renewed optimism toward nature-based green technology. Based on these relations, it is inferred that the application of earthworm-mediated vermitechnology increases sustainable development by strengthening the underlying economic, social and ecological framework. Graphic abstract